Searching for distant galaxy clusters: optical observations, cluster search algorithms and the cluster selection function - Falter, Siegfried (2006)
HIROCS is a multi-color survey designed to construct a statistically significant galaxy cluster sample for galaxy evolution studies using a multi-color classification scheme in the redshift range 0.5 < z < 1.5. After contributing to the survey specifications, tests of the multi-color classification with the observational setup showed the feasibility of the project. The photometric redshift accuracy of delta(z) = 0.076 was estimated at the R band limit of ~25 mag. The new algorithm for the galaxy cluster detection was developed and tested with COMBO-17 data. In the three COMBO-17 fields covering 0.78 square degrees 15 cluster candidates were identified in the redshift range 0.3 < z < 0.9. The power of the search method was demonstrated by a comparison with the cluster detections from the Voronoi tessellation. For the determination of the cluster selection function in HIROCS and COMBO-17 procedures to simulate galaxy clusters were introduced. Due to the lack of fully reduced HIROCS data, the COMBO-17 selection function was quantified; rich clusters are expected to be found in the redshift range covered by COMBO-17. First steps towards an analysis of cluster candidates were carried out using the COMBO-17 candidates. Finally, a rich cluster at redshift ~0.7 was identified in the first HIROCS infrared data.
Keywords: Hochschulschrift; Himmelsdurchmusterung; Galaxienhaufen